Mutation Profiles of eGFP-Tagged Small Ruminant Morbillivirus During 45 Serial Passages in Ribavirin-Treated Cells - Liu, Fuxiao; Zou, Yanli; Li, Lin; Liu, Chunju; Wu, Xiaodong (Frontiers in Veterinary Science, 2021)
Small ruminant morbillivirus (SRMV), formerly known as peste-des-petits-ruminants virus, classified into the genus Morbillivirus in the family Paramyxoviridae. Its L protein functions as the RNA-dependent RNA polymerases (RdRp) during viral replication. Due to the absence of efficient proofreading activity in their RdRps, various RNA viruses reveal high mutation frequencies, making them evolve rapidly during serial passages in cells, especially treated with a certain mutagen, like ribavirin. We have previously rescued a recombinant enhanced green fluorescence protein-tagged SRMV (rSRMV-eGFP) using reverse genetics. In this study, the rSRMV-eGFP was subjected to serial passages in ribavirin-treated cells. Due to the ribavirin-exerted selective pressure, it was speculated that viral progenies would form quasispecies after dozens of passages. Viral progenies at passage-10, -20, -30, -40, and -50 were separately subjected to next-generation sequencing (NGS), consequently revealing a total of 34 single-nucleotide variations, including five synonymous, 21 missense, and one non-sense mutations. The L sequence was found to harbor eight missense mutations during serial passaging. It was speculated that at least one high-fidelity variant was present in viral quasispecies at passage-50. If purified from the population of viral progenies, this putative variant would contribute to clarifying a molecular mechanism in viral high-fidelity replication in vitro.